The THE ROLE OF ASTAXANTHIN COMPARED WITH METFORMIN IN PREVENTING GLYCATED HUMAN SERUM ALBUMIN FROM POSSIBLE UNFOLDING: A MOLECULAR DYNAMIC STUDY - SYAHPUTRA WIBOWO; SRI WIDYARTI; AKHMAD SABARUDIN; DJOKO WAHONO SOEATMADJI; SUTIMAN BAMBANG SUMITRO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Albumin in diabetes mellitus undergoes conformational changes that affect the ability as an endogenous scavenger. Treatment with astaxanthin (ASX) expected to improve the function of albumin in case of diabetes mellitus. The objectives of this study are to compare the capability of ASX and metformin to prevent conformational changes on glycated albumin. Methods: Data mining is performed to obtain human serum albumin (HSA) (4K2C), glucose (79025), ASX (5281224), and metformin (4091). Data preparation used PyRx and Discovery Studio 2016 Client. PyRx is utilized for docking and analysis of receptor-ligand interactions with LigPlus and Discovery Studio 2016 Client. YASARA is used for molecular dynamics simulations with a running time of 15.000 ps. Results: A description of the glycated-HSA (gHSA) conformational changes that are bound to metformin has been successfully carried out. Changes that occur were unfolding and release of bonds in gHSA. Unfolding on gHSA includes the release of bonds between sites A and B. The root mean square deviation (RMSD) backbone value of metformin-gHSA shows a significant difference with gHSA at 8650 ps where gHSA showed 6.47 nm while the metformin-gHSA was 8.06 nm and continues to increase up to 15.72 nm at the end of the simulation. RMSD and root mean square fluctuation residues of gHSA which were interacted with ASX showed conditions close to normal HSA. In 11725 ps ASX-gHSA remained stable at 5.78 nm, whereas gHSA increased to 8.13 nm. gHSA at the end of the simulation showed a number of 9.052 nm while the normal HSA was 7.561 nm. Conclusion: This result indicated that ASX prevents gHSA from possible unfolding.